Polyclonal antibody-based dot-ELISA and immunocapture-RT-PCR for Cucumber green mottle mosaic virus detection - SHANG Hai-li; ZHOU Xue-ping; WU Jian-xiang (浙江大学学报. 农业与生命科学版, 2010)
Cucumber green mottle mosaic virus (CGMMV) is one of important viruses from cucurbit crops. Using purified CGMMV particles as immunogens, the polyclonal antibody (PAb) was prepared in New Zealand rabbits. The ELISA titer of the PAb was 1∶512 000. The PAb could specifically react with the 17.5 ku coat protein of CGMMV but not with the Tobacco mosaic virus, Odontoglossum ringspot virus and healthy plants. The PAb could detect successfully CGMMV in plant sap at 1∶40 960 dilution in indirect enzyme-linked immunosorbent assay (ACP-ELISA). On the basis of the prepared PAb against CGMMV, a dot-ELISA and an immunocapture-RT-PCR (IC-RT-PCR) were established for CGMMV detection. The dot-ELISA could detect CGMMV from infected leaf extract at dilution limit of 1∶10 240. A specific band with an expected size (480 bp) was amplified from the virus infected leaves by the established IC-RT-PCR, and the IC-RT-PCR could detect the viruses from the virus infected leaf extract at dilution limit of 1∶163 840. The two detection methods using the prepared PAb provide technical supports for the diagnosis and control of the CGMMV disease.